The simulated newsroom: A novel educational innovation to teach advocacy skills to resident physicians. Issue 4 (11th August 2022) - Bigham, Blair L.; Lavelle, Conor; Hulme, Jennifer; Hayman, Kate
Abstract: Need for Innovation: Advocacy is a key competency of Canadian residency education, yet physicians seldom engage with supraclinical advocacy efforts upon completion of training. Objective of innovation: The objective was to equip participants with the knowledge and skills required to engage as physician‐advocates in their communities using opinion writing as a tool. Developmental process: We used Kern's six‐step framework to leverage a common medical training method, simulation, to teach journalistic skills related to advocacy in our novel "simulated newsroom." Two emergency physicians with journalism training and workplace experience developed simulated newsroom workshops. The simulated newsroom consisted of participants acting as journalists and the expert facilitator acting as a news editor over two workshops. The participants were encouraged to write and workshop an article with colleagues. Evaluation: Participants were invited to participate in a semistructured focus group and to submit their article for qualitative analysis. Focus group transcripts and written work were qualitatively analyzed to understand acceptability and feasibility and how participants might engage as future health advocates. Outcomes: Twelve participants registered for the workshops and six attended. All six participated in the focus group; four submitted written work. The innovation bolstered participants' confidence in advocacy through the popular press and provided demonstrable skills in opinion writing. Participants valued the workshop as a voluntary component of residency education led by physicians with journalism expertise. Discussion: The simulated newsroom may be an effective mechanism for increasing confidence and competence in advocacy writing.